- - Ristivojević, Branislav; Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The authors of the paper examine a recent phenomenon in international criminal justice: the attemt to organize a trial for the crime of aggression in the context of the armed conflict in Ukraine. Currently, there is no institution within international criminal justice that has jurisdiction over this matter, prompting the expert community to propose several solutions. The authors analyze each proposal from different perspectives, focusing on the realization of the principle of legitimacy in establishing new judicial bodies or conducting trials for the crime of aggression before existing courts. This principle is particularly significant in international criminal law, perhaps even more so than in domestic criminal law. The authors conclude that each proposed solution raises concerns regarding legitimacy, as none of them meet the criteria commonly used to evaluate the realization of this principle. The most critical issues are consistency and responsibility. Consistency in promoting the ideals of global international justice is essential for proponents to avoid the perception that their proposals serve only narrow, selfish, or political interests. In many cases, the proposers are states that have previously committed acts of aggression without facing consequences and have supported the principle of non-responsibility in earlier proposals for establishing jurisdiction to prosecute such acts in international criminal justice, which unequivocally undermines the credibility of their current proposals. Finally, the authors present their original recommendation for addressing this situation. They suggest that, as with previous cases of aggression, resolution should occur through direct political engagement between the involved states. They emphasize that this particular case of aggression is unlikely to end with the unconditional surrender of one of the warring parties, which, as history from the International Military Tribunals in Nuremberg and Tokyo illustrates, is a necessary condition for effectively organizing trials for the crime of aggression.